Analysis of Factors Affecting Period on GHS Using PhET Simulation - Anzani, Yunita Ayudhia Anzani; Syahri Ramadhanti; Noval Mulya Dava (Sunan Kalijaga Journal of Physics, 2023)
Physics is one of the sciences that is studied based on facts, natural phenomena, ideas and results of experiments/experiments. Physics is a science that is closely related to everyday life, one of which is found in Simple Harmonic Motion which discusses pendulums on clocks and strings on guitars. Simple vibrations (GHS) are an example of periodic motion when the amplitude of vibrations in the system is relatively small and the displacement is less than 15°. GHS is a regular alternating motion through the equilibrium point and the number of vibrations in one second is always constant. If the movement occurs repeatedly within a certain time interval, it is called periodic motion. One of the experiments that can be done with simple vibrations is to make a mathematical pendulum or a simple pendulum. The method used in this research to determine the factors that affect the period of pendulum vibrations is a literature review and experiments using PhET simulations. The results of this study are data generated from experiments and calculations which state that the factors that affect the period of pendulum vibrations in simple harmonic motion are the length of the rope and the acceleration due to gravity. While the mass has no effect on the period of the pendulum vibration. The effect of the length of the string is directly proportional to the period of the pendulum's vibration, and the effect of gravity is inversely proportional to the period of the pendulum's vibration.